Disrupted trophic interactions affect recruitment of boreal deciduous and coniferous trees in northern Europe. Issue 4 (23rd March 2017) - Angelstam, Per; Manton, Michael; Pedersen, Simen; Elbakidze, Marine
Abstract: Loss of large carnivore populations may lead to increased population densities of large herbivores, and subsequent cascading effects on the composition, structure, and function of ecosystems. Using a macroecological approach based on studies in multiple boreal forest landscapes in the Baltic Sea region and Russia, we tested the hypothesis that disrupted trophic interactions among large carnivores and large herbivores affect the recruitment of both ecologically and economically valuable tree species. We measured damage levels on young trees and large herbivore density in 10 local landscapes representing a gradient from extinct to extant populations of both large carnivores and large herbivores. We also tested the alternative hypothesis that forest management intensity is correlated to reduced recruitment of these tree species. At the macroecological scale there was an inverse relationship between the number of large carnivores and large herbivores. This coincided with a steep gradient in browsing damage on the ecologically important aspen, rowan and sallow as hosts for specialized species, as well as the economically important Scots pine. In one landscape hunting had replaced the presence of carnivores. Mean damage levels of these four tree species were correlated with large herbivore abundance, but not with forest management intensity. We discuss the pros and cons of this macroecological approach, as well as the challenge of governing and managing trophic interactions at multiple scales.